Examining Senior High School Students’ Experiences Toward Learning Qualitative Research Methods - Alcazaren, Holden Kenneth G. (Alipato, A Journal of Basic Education; Vol 15 (2024): Alipato, A Journal of Basic Education, 2025)
As research is strengthened in the Senior High School (SHS) curriculum, there is a need to examine how students learn the concepts and skills in doing varied works related to it. This means investigating how classroom practices and activities greatly affect students’ learning experiences within a research class, particularly in developing their cognitive and affective competencies toward research (Messiou & Lowe, 2023; Vossen et al., 2018). To examine such a process in the Philippine educational setting, the present article explored the teaching and learning of Practical Research 1, an introductory course that focuses on qualitative research methods in SHS. In this qualitative exploratory study, a focus group discussion of 6 SHS students from the academic track was done. Using Biggs’ (2003) 3P model, the findings were categorized into presage, process, and product factors. Coming into this course, participants recounted how their past educational backgrounds and limited knowledge of research methods had affected the way they initially perceived the course. Moreover, the role of their teachers and the kind of activities they do in the classroom influenced their motivation and attitude toward research in general. Factoring in these experiences, all students still think that the course is beneficial in preparing them for their future academic and professional endeavors. Through this exploratory study, results were able to identify issues and improvements in the curriculum implementation of this research method class in the SHS.